Foundations of ethics programs for government in a liberal democracy. - Beauchamp, Denis L. (University of Ottawa (Canada), 2002)
Dennis Thompson says that the years since the 1960s have witnessed a "revival of concern about ethics" that has spread to all sectors of society. The nature of the "revival," however, raises many important and critical questions. Foremost among them is the question of what foundations are being proposed for institutionalizing ethics in government in a liberal democracy? The ethical values and principles promoted in these initiatives, as well as the ethical obligations they can generate, can only be as strong the foundations offered for these values and principles. In searching for these foundations in the public sector, the dissertation limits itself to and focuses on the executive branch of government in a liberal government. Chapter One starts with a review of the literature on public administration ethics produced in the twentieth century and examines why the discipline has not yet found a firm foundation for public administration ethics. Although most of the literature produced on the subject is mainly on public administration ethics in the United States, Chapter Five will focus on initiatives in the Canadian context. The results of the review suggest that finding a foundation for public administration ethics requires reopening the question of the relationship between ethics and political philosophy. The dissertation then turns to the works of liberal political philosophers to see what they could propose as foundations for ethics in liberal democratic government. To structure my research, I adopt Ronald Dworkin's distinction between continuity and discontinuity strategies for explaining the nature of the relationship between the ethical in our private lives with the ethical in the political domain. The dissertation interprets John Rawls's political liberalism as a discontinuity approach to reconciling the ethical in these two domains and concludes that such an approach cannot provide a firm foundation for ethics in liberal democratic government. The dissertation interprets the liberalism of Ronald Dworkin and of William Galston as examples of a continuity approach and concludes that a continuity approach possesses the best potential for identifying the nature of a foundation for ethics in liberal democratic government. However, it also concludes that both these liberal political philosophers leave out something important and necessary for such a foundation. The dissertation also reviews the work of other liberal political philosophers: Amy Gutmann, Dennis Thompson, and John Tomasi. A critical analysis of their work shows in what way the deliberative democracy theory of Amy Gutmann and Dennis Thompson and the work of John Tomasi on liberalism beyond liberal justice cannot serve as a foundation for ethics in liberal democratic government while at the same time arguing that they provide essential elements for any effort to institutionalize ethics in government in a liberal democracy. The review of the literature on public administration ethics and the critical assessment of the works of liberal political philosophers provide conceptual resources to propose a minimum framework for ethics programs for the executive branch of government in a liberal democracy. On the basis of this framework, the dissertation assesses two current Canadian federal government initiatives to institutionalize ethics in government in a liberal democracy: a public service-wide initiative called "Values and Ethics" and the Defence Ethics Program of the Department of National Defence.
Keywords: Philosophy.